2015
DOI: 10.1128/jvi.02035-15
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Enterovirus A71 Antigenic Determinants from Viral Evolution

Abstract: Human enterovirus A71 (EV-A71) belongs to the Enterovirus A species in the Picornaviridae family. Several vaccines against EV-A71, a disease causing severe neurological complications or even death, are currently under development and being tested in clinical trials, and preventative vaccination programs are expected to start soon. To characterize the potential for antigenic change of EV-A71, we compared the sequences of two antigenically diverse genotype B4 and B5 strains of EV-A71 and identified substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
(46 reference statements)
0
29
0
Order By: Relevance
“…Of note, the emergence of C4 in 2018 resulted in a severe outbreak that caused >130,000 hospitalizations and 17 deaths. The underlying mechanism that determines the emergence of certain subgenogroups in specific localities remains a puzzle; it may be a consequence of a complex interplay among the pathogen, the hosts, and public health response, of which antigenic evolution might play a role (26,27). The fact that all serum samples from subgenogroup B5-infected patients collected before 2018 could neutralize the 2018 C4 virus suggests that immunity developed as a consequence of natural infection with subgenogroup B5 could provide protection against subgenogroup C4.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the emergence of C4 in 2018 resulted in a severe outbreak that caused >130,000 hospitalizations and 17 deaths. The underlying mechanism that determines the emergence of certain subgenogroups in specific localities remains a puzzle; it may be a consequence of a complex interplay among the pathogen, the hosts, and public health response, of which antigenic evolution might play a role (26,27). The fact that all serum samples from subgenogroup B5-infected patients collected before 2018 could neutralize the 2018 C4 virus suggests that immunity developed as a consequence of natural infection with subgenogroup B5 could provide protection against subgenogroup C4.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest the difference in antigenic properties and the antigenic diversity among the various genotypes of EV-A71. Recently, Huang et. al.…”
Section: Antigenicitymentioning
confidence: 99%
“…1). By creating reverse-genetics EV-A71 viruses containing mutations at VP1-98 K, VP1-145Q, and VP1-164E, they had found that these mutants significantly decreased neutralizing titers by 4-fold against the antisera of 3 of the 6 healthy individuals [28]. However, it was also noted that none of the single mutation alone was responsible for the antigenic changes, but rather all 3 mutations cooperatively influence the viral antigenic phenotype.…”
Section: Antigenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…VP1-D31G confers growth and fitness advantages in the CNS in humans (46). In addition, we previously reported that genetic variations in VP1-K98E, -E145Q, and -D164E cooperatively cause antigenic change of EV-A71 (47). To minimize quasispecies of viral genomes, in this study we applied a codon-deoptimized genome and highfidelity 3D polymerase in a reverse genetics preparation to obtain a genetically stable vaccine seed candidate with low virulence.…”
mentioning
confidence: 99%